A supramolecular hydrogel with an ideally homogeneous 3D network structure based on a (cucurbit[8]uril) host-(tetrahedron-like) guest interaction. (21st June 2019) - Wang, Yingying; Xu, Qizhen; Chen, Taijun; Zuo, Yingying; Wang, Jianxin
Abstract: The synthesis process of hydrogels based on using supramolecular chemistry as a core has attained much attention because it does not need complex operation and harsh reaction conditions whilst cucurbituril as the fourth generation of the host units has attracted much interest due to its unique characteristics. In this work, a supramolecular hydrogel was designed and prepared by using cucurbit urea and 4-arm-PEG as precursors. We firstly synthesized cucurbit[8]uril, 4-arm-PEG-BPY 2+ and 4-arm-PEG-Pyr by condensation reaction and chemical cross-linking, and then used them to construct an ideally homogeneous three-dimensional network structure of hydrogels and meanwhile studied the mechanism and properties of the stable 1:1:1 ternary complex. And then mechanical and biological tests were conducted. The results showed that the obtained hydrogels not only had high mechanical strength but also good biocompatibility. Additionally, the result also showed that their ideal structures ware very suitable for drug-loading and drug-releasing.